Sensemaking em um contexto de declínio organizacional: narrativas da mídia e dos gestores de livrarias de Uberlândia – MG - Santos, Isabela Ladeia (2021)
This dissertation is structured in two articles based on the concept of sensemaking. The first article is a systematic review that seeks to analyze the concepts of weickian sensemaking and critical sensemaking (CSM), highlighting contradictions and points of contact. In this review, a retrospect of the concept proposed by Weick (1995) and the approaches of organizational sensemaking and critical sensemaking (CSM) are presented. This study contributes a research agenda for Weickian sensemaking studies by proposing an epistemological debate on the topic: prospective sensemaking studies and the narrative research on critical sensemaking. The second article grounded in the theoretical perspectives of organizational sensemaking and organizational decline. It considers the application of the concept of sensemaking in a context characterized by strategic changes, which reflect uncertainty and unpredictability, and generate ambiguous interpretations of events: organizational decline. This is understood as a critical moment in an organization. In this second article, the research problem is how managers of small bookstores construct meaning (sensemaking) of their organizations in a context that seems to configure the decline of these organizations? The objective is to analyze the construction of meaning (sensemaking) of managers of small bookstores in the city of Uberlândia - MG from macro narratives of the media about the decline of the bookstore sector. In the methodological procedures, the narrative research method is used to carry out an analysis of the journalistic narrative of the media about the book business in the country and to conduct narrative interviews with owners of small bookstores in the city of Uberlândia-MG. This study contributes to a dialogue between studies on sensemaking and organizational decline by showing the contradictions and commonalities of sensemaking at two levels of analysis: the macro narrative on the decline of the bookstore sector and the narratives of local bookstore managers based on aspects of identity construction, social nature of the environments, interpretation on "extracted clues" and temporality. The results show that, although the bookstore industry as a whole is facing changes in the digitalization of book sales and consumption, in addition to the arrival of the company Amazon in Brazil, the managers interpret these changes differently. Small bookstores began to specialize in niches and reduced their cost structure, while large bookstores sought to attract customers through price, which affected profit and did not bring the expected results for these large companies.